A permeable asphalt composition and a method for preparing the same

Through the synergistic effect of composite aggregate system and nano anti-aging agent, the problems of pore structure stability, mechanical properties and environmental protection of traditional permeable asphalt have been solved, and permeable asphalt material with high permeability, durability and low emission has been realized.

CN120622846BActive Publication Date: 2026-02-03FOSHAN ZHONGNAN CONSTR ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510785439.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2026-02-03
Estimated Expiration
2045-06-12

AI Technical Summary

Technical Problem

Traditional permeable asphalt materials have significant defects in terms of pore structure stability, mechanical properties and anti-aging properties, and the VOCs emissions during the production process are high, making it difficult to meet environmental protection requirements.

Method used

A composite aggregate system consisting of basalt, ceramsite, and recycled glass microspheres is used, combined with interface reinforcing agents such as sodium lignosulfonate and epoxidized cashew nut shell oil, and anti-aging agents such as nano-titanium dioxide tubes loaded with tea polyphenols. Through precise modification and mixing processes, a stable three-dimensional network and a dual protection mechanism are formed.

Benefits of technology

It significantly improves the pore structure stability and mechanical properties of permeable asphalt, reduces VOC emissions, extends service life and meets environmental protection standards, while maintaining high permeability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005446938730000121
    Figure BDA0005446938730000121
Patent Text Reader

Abstract

The application provides a water-permeable asphalt composition and a preparation method thereof, and the composition comprises the following components and mass fractions: 22-28 parts of base asphalt, 65-75 parts of modified composite aggregate, 3-4 parts of interface reinforcing agent, 1-2 parts of nano anti-aging agent, and 0.3-0.5 parts of antioxidant dibutyl hydroxytoluene, wherein the modified composite aggregate is compounded by basalt coarse aggregate, ceramsite fine aggregate and recycled glass microbeads at a mass ratio of 5-7:3-5:1. Through the synergistic effect of the multistage aggregate compounding system, the bio-based interface reinforcing technology and the nano drug-loaded anti-aging process, the mechanical strength and durability are significantly improved while the high water permeability is maintained, and the low-temperature modification and solid waste recycling technology are used to realize the environment-friendly and low-consumption production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of road engineering materials technology, specifically relating to a permeable asphalt composition and its preparation method. Background Technology

[0002] Permeable asphalt, as a core material for sponge city construction, has the core function of rapidly infiltrating rainwater and alleviating urban flooding, while also needing to withstand vehicle loads and possess long-term durability. Traditional permeable asphalt is usually made by simply mixing single-graded aggregate with base asphalt. This type of material has been found to have significant defects in practical applications: First, its pore structure has poor stability, with the permeability coefficient decreasing by more than 50% after 3-6 months of use, mainly due to fine particles clogging the pore channels; second, its mechanical properties are insufficient, with commercially available products generally having a compressive strength below 12MPa, making it prone to aggregate detachment in areas frequently subjected to heavy vehicle traffic; more seriously, long-term ultraviolet radiation causes asphalt components to age, manifesting as surface powdering and cracking, shortening its service life to 2-3 years.

[0003] Existing improvement technologies mainly focus on the following three directions: First, polymer-modified asphalt, such as the SBS modification scheme disclosed in a certain literature, which raises the softening point of asphalt to above 70℃. However, SBS is prone to chain scission degradation during high-temperature mixing, and the increased viscosity of modified asphalt leads to uneven aggregate coating. Second, fiber-reinforcing materials are added, such as the polyester fiber doping technology proposed in a certain patent. Although it can improve crack resistance, the fibers are difficult to disperse in the mixture, forming local agglomerates that damage pore connectivity. Third, chemical anti-stripping agents are introduced. For example, a study used alkylamine compounds to improve the asphalt-aggregate interface bonding. However, these compounds are easily dissolved under rainwater immersion, causing groundwater pollution.

[0004] It is worth noting that in recent years, environmental regulations have become increasingly stringent in restricting VOC emissions from building materials. However, the current production process of permeable asphalt commonly uses petroleum-based solvents (such as coal tar and aromatic oils) as additive carriers, resulting in VOC emissions concentrations as high as 200-300 mg / m³ during construction. 3 In addition, traditional aggregate modification technologies often employ acid washing or alkali washing processes. For example, one approach uses 10% hydrochloric acid to treat limestone aggregates to enhance adhesion, but residual acidic substances can accelerate asphalt oxidation, and wastewater treatment costs are high.

[0005] Therefore, it is necessary to design a permeable asphalt composition and its preparation method. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, a permeable asphalt composition and its preparation method are provided.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A permeable asphalt composition comprising the following components and parts by weight: 22-28 parts of base asphalt, 65-75 parts of modified composite aggregate, 3-4 parts of interface reinforcing agent, 1-2 parts of nano anti-aging agent, and 0.3-0.5 parts of antioxidant dibutylhydroxytoluene, wherein the modified composite aggregate is composed of basalt coarse aggregate, ceramsite fine aggregate, and recycled glass microspheres in a mass ratio of 5-7:3-5:1.

[0009] The basalt coarse aggregate is pretreated with a silane coupling agent. The pretreatment process includes the following steps:

[0010] a) Immerse basalt aggregate with a particle size of 4-6 mm in a KH-550 silane coupling agent ethanol solution with a mass concentration of 1.5%-2.5% and the liquid-solid ratio of basalt aggregate to solution is 3-5:1.

[0011] b) Treat in an ultrasonic cleaner at a frequency of 40kHz for 20-30 minutes;

[0012] c) Remove the aggregate and dry it in an oven at 110-120℃ until the moisture content is ≤0.5%.

[0013] The recycled glass microspheres have a particle size of 0.8-1.2 mm, and their surface is etched with hydrofluoric acid at a concentration of 5%-8% for 10-15 minutes. After etching, the surface is passivated with water glass solution.

[0014] The interface enhancer is a compound of sodium lignosulfonate and epoxidized cashew nut shell oil at a mass ratio of 1:1.2-1.8. During compounding, sodium lignosulfonate is first dissolved in hot water at 60-70℃ to form a 15% mass concentration solution, and then mixed and emulsified with epoxidized cashew nut shell oil preheated to 80-90℃. The emulsification process is carried out in a shear emulsifier, with the rotation speed controlled at 8000-12000 r / min, the emulsification time at 8-12 minutes, and the emulsification temperature maintained at 70±2℃.

[0015] The nano-anti-aging agent is titanium dioxide nanotubes loaded with tea polyphenols, and its preparation method includes the following steps:

[0016] a) After pulverizing the tea leaves, mix them with 60% ethanol solution at a mass ratio of 1:10, and reflux extract at 75℃ for 2 hours;

[0017] b) After the extract from the previous step is adsorbed onto a macroporous resin, it is eluted with 80% ethanol to obtain a concentrated tea polyphenol.

[0018] c) Immerse titanium dioxide nanotubes in an ethanol solution containing 1%-2% tea polyphenols and sonicate at 50°C for 1 hour.

[0019] d) Centrifuge to collect the complex, and dry it at 60°C under nitrogen protection to constant weight. The result is titanium dioxide nanotubes loaded with tea polyphenols.

[0020] The titanium dioxide nanotubes have a diameter of 8-12 nm, a length of 200-300 nm, and a specific surface area ≥250 m². 2 / g.

[0021] The preparation of the ceramsite fine aggregate includes the following steps: sewage treatment plant sludge and shale are mixed and granulated at a mass ratio of 1:2-3, sintered in a rotary kiln at 1050-1100℃ for 25-30 minutes, and immediately immersed in a 5% silica sol for quenching treatment after exiting the kiln. The material temperature needs to be maintained above 600℃ during the quenching treatment in the silica sol, and the immersion time is 30-45 seconds; then, it is calcined again at 300℃ for 1 hour and crushed to a particle size of 2-3mm. The resulting ceramsite fine aggregate is the ceramsite fine aggregate.

[0022] A method for preparing a permeable asphalt composition, the method comprising the following steps:

[0023] a) Base asphalt pretreatment: Heat No. 70 road asphalt to 160-165℃, add antioxidant dibutylhydroxytoluene, and stir for 30-40 minutes;

[0024] b) Aggregate modification treatment: Pre-mix the pre-treated basalt coarse aggregate, ceramsite fine aggregate and recycled glass microspheres in a twin-helix mixer at 95-105℃ for 15-20 minutes to obtain modified composite aggregate.

[0025] c) Asphalt composite modification: Add the interface reinforcing agent to the pretreated base asphalt in three parts, with an interval of 5 minutes between each addition. During this period, maintain a stirring speed of 200-300 r / min. After the addition is complete, raise the temperature to 170-175℃ and keep it at that temperature for 20 minutes to obtain the modified asphalt.

[0026] d) Mixing and molding: After preheating the modified composite aggregate to 130-135℃, add it together with the modified asphalt into a planetary mixer and mix for 50-60 seconds at a pressure of 0.4-0.6MPa and a speed of 35-45r / min.

[0027] e) Functional treatment: Immediately after mixing, spread nano anti-aging agent and use a road roller to initially compact at 110-120℃.

[0028] The specific steps for adding the interface enhancer in step c are as follows: add 40% of the total amount of interface enhancer for the first time, add 30% for the second time, and add 30% for the third time. After each addition, the stirring speed should be increased to 500 r / min and maintained for 2 minutes.

[0029] The gap between the mixing blades and the cylinder wall of the planetary mixer is controlled at 3-5mm, and the cylinder jacket is circulated with heat transfer oil to maintain the temperature at 130±2℃.

[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:

[0031] 1. This application designs a composite aggregate system with optimized pore structure, employing a precise gradation of basalt, ceramsite, and recycled glass microspheres to form a stable three-dimensional network through complementary particle sizes. Basalt serves as the main framework, providing mechanical support; the silica sol coating on the surface of the ceramsite enhances interfacial bonding; and the microspheres fill the microscopic gaps, forming capillary water-conducting channels. This structure ensures an effective porosity of over 20% while simultaneously increasing compressive strength by approximately 40% through optimized mechanical conduction paths, effectively resolving the contradiction between permeability and strength.

[0032] 2. Addressing the issue of weak interfacial adhesion, the innovative interfacial reinforcing agent developed in this application plays a crucial role. The polar groups of sodium lignosulfonate form chemical bonds with the aggregate surface, while the long-chain molecules of epoxidized cashew nutshell oil penetrate into the asphalt cementitious phase to form an interpenetrating network. The synergistic effect of these two agents increases the asphalt-aggregate interfacial shear strength to 2.3 times that of traditional materials. Particularly under humid and hot conditions, this bio-based composite system exhibits superior water damage resistance, reducing pavement spalling rate by more than 60%.

[0033] 3. Regarding the improvement of anti-aging performance, this application creates a dual protection mechanism through nano-titanium dioxide tubes loaded with tea polyphenols. The semiconductor properties of the nanotubes can absorb ultraviolet energy, while tea polyphenol molecules capture free radicals through phenolic hydroxyl groups. The synergistic effect of the two reduces the asphalt aging index by 55%. More importantly, this loading structure achieves the sustained-release function of active ingredients, maintaining more than 80% free radical scavenging capacity in simulated aging tests lasting up to 5 years.

[0034] 4. The phased introduction of the interface reinforcing agent in the preparation process of this application, combined with precise temperature control, avoids the decomposition of bio-based components caused by high temperatures while ensuring the uniform dispersion of the modifier in the asphalt. The special structural design of the planetary mixer, combined with gap control and temperature field optimization, controls the asphalt film thickness on the aggregate surface within the optimal range of 15-20 μm, reducing the film thickness fluctuation range by 70% compared to traditional processes. This is crucial for ensuring the homogeneity of the material.

[0035] 5. The recycling of recycled glass microspheres in this application, combined with the technology for preparing ceramsite from wastewater treatment sludge, achieves a solid waste utilization rate of over 45%. The entire production process completely eliminates petroleum-based solvents, employing a water-based emulsification system, thus reducing VOC emissions from the industry average of 250 mg / m³. 3 Reduced to less than 30 mg / m 3In particular, the quenched ceramic particles form a silicon-oxygen network structure on their surface. This inorganic coating effectively blocks the precipitation of heavy metal ions, and the concentration of pollutants in the leachate meets the Class III standard for surface water.

[0036] 6. Improved durability is attributed to a systematic damage-resistant design. The gradient pore structure possesses self-cleaning capabilities, with micropores smaller than 2mm accounting for less than 15%, ensuring water permeability while significantly reducing the risk of fine particle clogging. The process design of spreading the nano-anti-aging agent on the surface during the later stages of mixing ensures its concentration in the 1-2mm area of ​​the road surface, specifically protecting the surface layer with the strongest UV radiation, increasing the utilization rate of the protective agent per unit area by more than 3 times.

[0037] 7. This invention achieves environmentally friendly and low-consumption production by leveraging the synergistic effects of a multi-level aggregate compounding system, bio-based interface enhancement technology, and nano-drug-loaded anti-aging process, while maintaining high permeability. It also utilizes low-temperature modification and solid waste recycling technologies. Detailed Implementation

[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0039] The sources of various raw materials in this application are briefly described as follows:

[0040] KH-550 silane coupling agent: purchased from Shanghai Yuyu New Material Technology Co., Ltd., CAS number 1760-24-3, model YUS-550.

[0041] Hydrofluoric acid: purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 7664-39-3, concentration 40%, type AR.

[0042] Water glass solution: purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 1344-09-8, modulus 3.3, industrial grade.

[0043] Sodium lignosulfonate: purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 8061-51-6, model L2010.

[0044] Epoxidized cashew nut shell oil: purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 8016-11-3, epoxy value 4.5%, model E2390.

[0045] Titanium dioxide nanotubes: purchased from Aladdin Biochemical Technology Co., Ltd., CAS number 13463-67-7, tube diameter 10nm, model T107557.

[0046] Macroporous resin: purchased from Aladdin Biochemical Technology Co., Ltd., model D101 styrene-based adsorption resin.

[0047] Butylhydroxytoluene: purchased from Shanghai Yuyu New Materials Technology Co., Ltd., CAS No. 128-37-0, model number DB-01.

[0048] Silica sol: Purchased from Shanghai Yuyu New Materials Technology Co., Ltd., CAS No. 112945-52-5, silica content 30%, model S-30.

[0049] Ethanol: Purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 64-17-5, purity ≥99.7%, grade AR.

[0050] Heat transfer oil: purchased from Sinopec Great Wall Lubricating Oil Company, model L-QD330, operating temperature range -20℃ to 320℃.

[0051] The sludge and shale from the wastewater treatment plant were purchased on-site as engineering-grade raw materials, while the recycled glass microspheres were recycled glass products.

[0052] A permeable asphalt composition comprising the following components and parts by weight: 22-28 parts of base asphalt, 65-75 parts of modified composite aggregate, 3-4 parts of interface reinforcing agent, 1-2 parts of nano anti-aging agent, and 0.3-0.5 parts of antioxidant dibutylhydroxytoluene, wherein the modified composite aggregate is composed of basalt coarse aggregate, ceramsite fine aggregate, and recycled glass microspheres in a mass ratio of 5-7:3-5:1.

[0053] The basalt coarse aggregate is pretreated with a silane coupling agent. The pretreatment process includes the following steps:

[0054] a) Immerse basalt aggregate with a particle size of 4-6 mm in a KH-550 silane coupling agent ethanol solution with a mass concentration of 1.5%-2.5% and the liquid-solid ratio of basalt aggregate to solution is 3-5:1.

[0055] b) Treat in an ultrasonic cleaner at a frequency of 40kHz for 20-30 minutes;

[0056] c) Remove the aggregate and dry it in an oven at 110-120℃ until the moisture content is ≤0.5%.

[0057] The recycled glass microspheres have a particle size of 0.8-1.2 mm, and their surface is etched with hydrofluoric acid at a concentration of 5%-8% for 10-15 minutes. After etching, the surface is passivated with water glass solution.

[0058] The interface enhancer is a compound of sodium lignosulfonate and epoxidized cashew nut shell oil at a mass ratio of 1:1.2-1.8. During compounding, sodium lignosulfonate is first dissolved in hot water at 60-70℃ to form a 15% mass concentration solution, and then mixed and emulsified with epoxidized cashew nut shell oil preheated to 80-90℃. The emulsification process is carried out in a shear emulsifier, with the rotation speed controlled at 8000-12000 r / min, the emulsification time at 8-12 minutes, and the emulsification temperature maintained at 70±2℃.

[0059] The nano-anti-aging agent is titanium dioxide nanotubes loaded with tea polyphenols, and its preparation method includes the following steps:

[0060] a) After pulverizing the tea leaves, mix them with 60% ethanol solution at a mass ratio of 1:10, and reflux extract at 75℃ for 2 hours;

[0061] b) After the extract from the previous step is adsorbed onto a macroporous resin, it is eluted with 80% ethanol to obtain a concentrated tea polyphenol.

[0062] c) Immerse titanium dioxide nanotubes in an ethanol solution containing 1%-2% tea polyphenols and sonicate at 50°C for 1 hour.

[0063] d) Centrifuge to collect the complex, and dry it at 60°C under nitrogen protection to constant weight. The result is titanium dioxide nanotubes loaded with tea polyphenols.

[0064] The titanium dioxide nanotubes have a diameter of 8-12 nm, a length of 200-300 nm, and a specific surface area ≥250 m². 2 / g.

[0065] The preparation of the ceramsite fine aggregate includes the following steps: sewage treatment plant sludge and shale are mixed and granulated at a mass ratio of 1:2-3, sintered in a rotary kiln at 1050-1100℃ for 25-30 minutes, and immediately immersed in a 5% silica sol for quenching treatment after exiting the kiln. The material temperature needs to be maintained above 600℃ during the quenching treatment in the silica sol, and the immersion time is 30-45 seconds; then, it is calcined again at 300℃ for 1 hour and crushed to a particle size of 2-3mm. The resulting ceramsite fine aggregate is the ceramsite fine aggregate.

[0066] A method for preparing a permeable asphalt composition, the method comprising the following steps:

[0067] a) Base asphalt pretreatment: Heat No. 70 road asphalt to 160-165℃, add antioxidant dibutylhydroxytoluene, and stir for 30-40 minutes;

[0068] b) Aggregate modification treatment: Pre-mix the pre-treated basalt coarse aggregate, ceramsite fine aggregate and recycled glass microspheres in a twin-helix mixer at 95-105℃ for 15-20 minutes to obtain modified composite aggregate.

[0069] c) Asphalt composite modification: Add the interface reinforcing agent to the pretreated base asphalt in three parts, with an interval of 5 minutes between each addition. During this period, maintain a stirring speed of 200-300 r / min. After the addition is complete, raise the temperature to 170-175℃ and keep it at that temperature for 20 minutes to obtain the modified asphalt.

[0070] d) Mixing and molding: After preheating the modified composite aggregate to 130-135℃, add it together with the modified asphalt into a planetary mixer and mix for 50-60 seconds at a pressure of 0.4-0.6MPa and a speed of 35-45r / min.

[0071] e) Functional treatment: Immediately after mixing, spread nano anti-aging agent and use a road roller to initially compact at 110-120℃.

[0072] The specific steps for adding the interface enhancer in step c are as follows: add 40% of the total amount of interface enhancer for the first time, add 30% for the second time, and add 30% for the third time. After each addition, the stirring speed should be increased to 500 r / min and maintained for 2 minutes.

[0073] The gap between the mixing blades and the cylinder wall of the planetary mixer is controlled at 3-5mm, and the cylinder jacket is circulated with heat transfer oil to maintain the temperature at 130±2℃.

[0074] In terms of economic benefits, the cost of the bio-based interface agent in this application is only 60% of that of traditional petroleum resin, and the preparation process does not require specialized equipment. The concentration of the silane coupling agent used in aggregate modification is controlled within the critical range of 1.5-2.5%, ensuring both the modification effect and avoiding cost waste caused by excessive use. More than 90% of the raw materials in the entire formulation system can be sourced locally, reducing logistics costs to 70% of the industry average.

[0075] From a life-cycle perspective, the maintenance period of this permeable asphalt pavement can be extended to 8-10 years, reducing the number of major repairs by more than two. Especially in areas prone to acid rain, the silica sol protective layer on the surface of the expanded clay aggregate can neutralize acidic substances, reducing the material mass loss rate from 1.2% per year to below 0.3%. The addition of recycled glass microspheres also endows the pavement with moderate elastic deformation capacity, maintaining a deformation recovery rate of over 3% even at -20℃, significantly reducing the risk of cracking caused by temperature stress.

[0076] This application, based on in-depth research into the failure mechanism of permeable asphalt, achieves a performance breakthrough through multi-dimensional matching of materials, structure, and process. The synergistic effect of each component produces a result greater than the sum of its parts. For example, the combined use of nanotube drug-carrying systems and bio-based interface agents forms a three-dimensional protective network at the molecular level, which is impossible to achieve with single-component modification. Precise control of temperature field and shear force in the preparation process further ensures the effective functioning of each component, perfectly transforming laboratory research results into engineering application value.

[0077] The technical solutions of the present invention are further illustrated below through examples and comparative examples, but the scope of protection of the present invention is not limited thereto.

[0078] Example 1

[0079] Twenty-two parts of No. 70 road asphalt were selected as the base asphalt, and basalt coarse aggregate, ceramsite fine aggregate, and recycled glass microspheres were compounded at a mass ratio of 7:5:1. Basalt pretreatment involved a 2.5% KH-550 solution with a liquid-to-solid ratio of 3:1, ultrasonic treatment for 30 minutes, followed by drying at 120℃. Recycled glass microspheres were etched with 8% hydrofluoric acid for 10 minutes and passivated with water glass for 45 seconds. The interface reinforcing agent was a mixture of sodium lignosulfonate and epoxidized cashew nutshell oil at a ratio of 1:1.8, emulsified at 12000 r / min for 12 minutes. The nano-anti-aging agent was prepared using a 2% tea polyphenol loading and titanium dioxide nanotubes with a diameter of 12 nm. In the preparation of the ceramsite fine aggregate, sludge and shale were mixed at a ratio of 1:3, sintered in a rotary kiln at 1100℃ for 30 minutes, and the material temperature was maintained at 620℃ during silica sol quenching. During preparation, the base asphalt is preheated to 165℃, and the interface reinforcing agent is added in three batches, with an interval of 5 minutes between each batch. The planetary mixer has a gap of 5mm and a mixing pressure of 0.6MPa.

[0080] Example 2

[0081] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:

[0082] The process used 28 parts of base asphalt with an aggregate ratio of 5:3:1. The basalt pretreatment solution concentration was 1.5%, with a liquid-to-solid ratio of 5:1, ultrasonicated for 20 minutes, and dried at 110℃. Regenerated glass microspheres were etched at a concentration of 5% for 15 minutes, followed by passivation for 30 seconds. An interface reinforcing agent with a ratio of 1:1.2 was applied, and the mixture was emulsified at 8000 rpm for 8 minutes. Nanotubes with a diameter of 10 nm and a tea polyphenol loading of 1% were used. Ceramsite raw material was mixed at a ratio of 1:2.5, sintered at 1050℃ for 25 minutes, and quenched at 600℃. The base asphalt was heated to 163℃, with a planetary stirrer gap of 4 mm and a mixing pressure of 0.5 MPa.

[0083] Example 3

[0084] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:

[0085] 25 parts of base asphalt, aggregate ratio 6:4:1. Basalt treatment concentration 2.0%, liquid-to-solid ratio 4:1, ultrasonic treatment for 25 minutes, drying at 115℃. Glass microsphere etching concentration 6%, treatment for 12 minutes, passivation for 38 seconds. Interface reinforcing agent ratio 1:1.5, emulsification speed 10000 r / min, treatment for 10 minutes. Nanotube diameter 8 nm, tea polyphenol loading 1.5%. Ceramsite raw material ratio 1:2, sintering temperature 1075℃ for 28 minutes, quenching temperature 610℃. Base asphalt heated to 160℃, planetary stirring gap 3 mm, mixing pressure 0.4 MPa.

[0086] Comparative Example 1

[0087] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:

[0088] The aggregate used is a single type of basalt with a particle size of 4-6mm, without the addition of ceramsite or glass microspheres. The interface reinforcing agent is replaced with an equal amount of petroleum resin.

[0089] Comparative Example 2

[0090] In this comparative example, the similarities with Example 2 will not be repeated, and the differences are as follows:

[0091] The step of adding the interface enhancer was omitted, and the aggregate and matrix asphalt were directly mixed. The nano anti-aging agent was replaced with ordinary titanium dioxide powder, and tea polyphenol loading was not performed.

[0092] Comparative Example 3

[0093] In this comparative example, the similarities with Example 3 will not be repeated, and the differences are as follows:

[0094] The basalt pretreatment was changed to soaking in 10% hydrochloric acid for 30 minutes, and no silane coupling agent was used. The ceramsite fine aggregate was not subjected to silica sol quenching treatment.

[0095] Comparative Example 4

[0096] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:

[0097] All interfacial reinforcing agents were added at once during preparation, and the stirring speed was maintained at 200 r / min without phased acceleration. The planetary mixer gap was increased to 8 mm.

[0098] Comparative Example 5

[0099] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:

[0100] Recycled glass microspheres were replaced with an equal amount of quartz sand, with a particle size of 0.8-1.2 mm, without surface etching treatment. The application rate of the nano-anti-aging agent was increased to 300 g per square meter.

[0101] Performance Test Results and Analysis

[0102] The permeable asphalt compositions obtained according to the parameters of the examples and comparative examples were tested respectively, and the test results are shown in Table 1.

[0103] Table 1 Analysis of Test Results

[0104]

[0105] As shown in Table 1, in terms of permeability, the permeability coefficients of Examples 1-3 all exceeded 0.8 cm / s, significantly higher than the 0.3-0.5 cm / s of traditional materials. In particular, Example 2, using smaller-sized aggregates, formed a denser water-conducting channel. Comparative Example 1, lacking multi-stage aggregate formulation, showed a significant decrease in permeability coefficient, verifying the necessity of the composite aggregate system. Compressive strength data showed that Example 1 reached 24.3 MPa, a 60% increase compared to Comparative Example 1. This is attributed to the synergistic effect of the basalt skeleton's mechanical support and the interface reinforcing agent. Comparative Example 4, due to the lack of staged addition of modifiers, resulted in uneven asphalt coating and a 18% decrease in strength.

[0106] In the aging index test, the 12.5% ​​of Example 1 was significantly lower than the 35.6% of Comparative Example 2, confirming the effectiveness of the dual protection mechanism of the drug-loaded nanotubes. Although Comparative Example 5 increased the amount of anti-aging agent, its protective effect was actually inferior to Example 2 because it did not employ a sustained-release structure. Environmental indicators showed that the VOC emissions of the example groups were only 10%-15% of those of the traditional process. Comparative Example 2, due to the use of petroleum resin instead of bio-based interface agents, saw its emissions surge to 205 mg / m³. 3 This highlights the environmental advantages of the invention. The pore blockage rate data confirms the self-cleaning function of the gradient pore structure. After 6 months of use, Example 1 showed a blockage rate of only 8.7%, while Comparative Example 3, due to the lack of aggregate surface modification, had a blockage rate as high as 19.3%, as fine particles adhered more easily.

[0107] In summary, Example 3 demonstrates balanced performance across all indicators, with permeability and compressive strength improved by 76% and 97% respectively compared to industry standards, and an aging rate reduced to one-third that of traditional materials. The comparative data conversely validates the indispensable technical characteristics of the composite modification system, such as the necessity of key innovations like the staged addition of the interface reinforcing agent and the aggregate surface treatment process. In particular, when the synergy of the material system is disrupted (e.g., by changing the process parameters in Comparative Example 4), the performance indicators show a precipitous decline, proving that the technical solution of this invention possesses a rigorous systematic nature and is indivisible.

[0108] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A permeable asphalt composition, characterized in that, The composition comprises the following components and parts by weight: 22-28 parts of base asphalt, 65-75 parts of modified composite aggregate, 3-4 parts of interface reinforcing agent, 1-2 parts of nano anti-aging agent, and 0.3-0.5 parts of antioxidant dibutylhydroxytoluene, wherein the modified composite aggregate is composed of basalt coarse aggregate, ceramsite fine aggregate and recycled glass microspheres in a mass ratio of 5-7:3-5:1; The interface enhancer is a compound of sodium lignosulfonate and epoxidized cashew nut shell oil at a mass ratio of 1:1.2-1.8; The nano-anti-aging agent is titanium dioxide nanotubes loaded with tea polyphenols; The preparation of the ceramsite fine aggregate includes the following steps: Sewage treatment plant sludge and shale are mixed at a mass ratio of 1:2-3 and granulated. The mixture is then sintered in a rotary kiln at 1050-1100℃ for 25-30 minutes. After exiting the kiln, the mixture is immediately immersed in a 5% silica sol solution for quenching. During the quenching process in the silica sol solution, the material temperature must be maintained above 600℃, and the immersion time is 30-45 seconds. Then, the mixture is calcined again at 300℃ for 1 hour and crushed to a particle size of 2-3 mm. The resulting ceramsite fine aggregate is obtained.

2. The permeable asphalt composition according to claim 1, characterized in that: The basalt coarse aggregate is pretreated with a silane coupling agent. The pretreatment process includes the following steps: a) Immerse basalt aggregate with a particle size of 4-6 mm in a KH-550 silane coupling agent ethanol solution with a mass concentration of 1.5%-2.5% and the liquid-solid ratio of basalt aggregate to solution is 3-5:

1. b) Treat in an ultrasonic cleaner at a frequency of 40kHz for 20-30 minutes; c) Remove the aggregate and dry it in an oven at 110-120℃ until the moisture content is ≤0.5%.

3. The permeable asphalt composition according to claim 1, characterized in that: The recycled glass microspheres have a particle size of 0.8-1.2 mm, and their surface is etched with hydrofluoric acid at a concentration of 5%-8% for 10-15 minutes. After etching, the surface is passivated with water glass solution.

4. The permeable asphalt composition according to claim 1, characterized in that: When compounding sodium lignosulfonate with epoxidized cashew nut shell oil, sodium lignosulfonate is first dissolved in hot water at 60-70℃ to form a 15% (w / w) solution, and then mixed and emulsified with epoxidized cashew nut shell oil preheated to 80-90℃. The emulsification process is carried out in a shear emulsifier, with the rotation speed controlled at 8000-12000 r / min, the emulsification time at 8-12 minutes, and the emulsification temperature maintained at 70±2℃.

5. The permeable asphalt composition according to claim 1, characterized in that, The specific preparation method of the nano-anti-aging agent includes the following steps: a) After pulverizing the tea leaves, mix them with 60% ethanol solution at a mass ratio of 1:10, and reflux extract at 75℃ for 2 hours; b) After the extract from the previous step is adsorbed onto a macroporous resin, it is eluted with 80% ethanol to obtain a concentrated tea polyphenol. c) Immerse titanium dioxide nanotubes in an ethanol solution containing 1%-2% tea polyphenols and sonicate at 50°C for 1 hour. d) Collect the complex by centrifugation and dry it at 60°C under nitrogen protection until constant weight. The result is titanium dioxide nanotubes loaded with tea polyphenols.

6. The permeable asphalt composition according to claim 5, characterized in that: The titanium dioxide nanotubes have a diameter of 8-12 nm, a length of 200-300 nm, and a specific surface area of ​​≥250 m² / g.

7. A method for preparing the permeable asphalt composition according to any one of claims 1-6, characterized in that, The method includes the following steps: a) Base asphalt pretreatment: Heat No. 70 road asphalt to 160-165℃, add antioxidant dibutylhydroxytoluene, and stir for 30-40 minutes; b) Aggregate modification treatment: Pre-mix the pre-treated basalt coarse aggregate, ceramsite fine aggregate and recycled glass microspheres in a twin-helix mixer at 95-105℃ for 15-20 minutes to obtain modified composite aggregate. c) Asphalt composite modification: Add the interface reinforcing agent to the pretreated base asphalt in three parts, with an interval of 5 minutes between each addition. During this period, maintain a stirring speed of 200-300 r / min. After the addition is complete, heat the asphalt to 170-175℃ and keep it at that temperature for 20 minutes to obtain the modified asphalt. d) Mixing and molding: After preheating the modified composite aggregate to 130-135℃, add it together with the modified asphalt into a planetary mixer and mix for 50-60 seconds at a pressure of 0.4-0.6MPa and a speed of 35-45r / min. e) Functional treatment: Immediately after mixing, spread nano anti-aging agent and use a road roller to initially compact at 110-120℃.

8. The method for preparing a permeable asphalt composition according to claim 7, characterized in that, The specific steps for adding the interface enhancer in step c are as follows: add 40% of the total amount of interface enhancer for the first time, 30% for the second time, and 30% for the third time. After each addition, the stirring speed should be increased to 500 r / min and maintained for 2 minutes.

9. The method for preparing a permeable asphalt composition according to claim 8, characterized in that: The gap between the mixing blades and the cylinder wall of the planetary mixer is controlled at 3-5mm, and the cylinder jacket is circulated with heat transfer oil to maintain the temperature at 130±2℃.

Citation Information

Patent Citations

  • Highly-wear-resistant styrene-butadiene rubber and preparation method thereof

    CN108084527A

  • Antibacterial packaging material and preparation method thereof

    CN119371752A